A existência de fórmulas por radicais para resolução das equações algébricas - Costa, Polyana de Castro (2020)
In this work we will present a bibliographic review on the emergence of algebraic equati- ons and the deduction of formulas by radicals to solve equations of second degree, third degree and fourth degree. Then, we will present how the study of the equations in Modern Algebra followed, on the contributions of Abel and Galois, for understanding the inexis- tence of a formulas by radicals for solving equations of grade 5 or higher. Highlighting the importance of group theory in clarifying the question of the algebraic resolution of the equations.